2005
DOI: 10.1079/bjn20051447
|View full text |Cite
|
Sign up to set email alerts
|

The expression of growth-arrest genes in the liver and kidney of the protein-restricted rat fetus

Abstract: During fetal life, there are periods of rapid cell proliferation, which are uniquely sensitive to nutritional perturbation. Feeding the pregnant rat a proteinrestricted diet alters the growth trajectory of major fetal organs such as the kidney. By day 21 of gestation, the ratio of kidney weight to total body weight is reduced in the fetuses of dams fed a protein-deficient diet. In contrast, the ratio of fetal liver weight to total body weight is unchanged. To investigate the mechanisms underlying this dispropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Previously, it has been shown that feeding the pregnant rat the protein-restricted diets described above alters the growth trajectory of the fetus [11,12]. By day 21 of gestation, there are significant asymmetries in the growth of major organs.…”
Section: Introductionmentioning
confidence: 97%
“…Previously, it has been shown that feeding the pregnant rat the protein-restricted diets described above alters the growth trajectory of the fetus [11,12]. By day 21 of gestation, there are significant asymmetries in the growth of major organs.…”
Section: Introductionmentioning
confidence: 97%
“…Analyses of foetal liver were carried out on tissues from six female pups, one chosen randomly from each litter. Females were used as these were shown to be more affected in adult life [11].…”
Section: Methodsmentioning
confidence: 99%
“…All mRNA samples used had an RNA integrity number [8 (Agilent Bioanalyser) and sexing was verified by PCR [11]. Samples of RNA were hybridised to Affymetrix Rat Genome 230 2.0 microarrays (Affymetrix, Santa Clara, CA, USA, provided through the NuGO array pipeline) by ServiceXS (Leiden, the Netherlands).…”
Section: Microarray Analysis Of Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns órgãos de fetos podem ser mais sensíveis que outros quando dietas com conteúdo de proteína balanceado com metionina é administrada a fêmeas durante a gravidez (MALONEY et al, 2005 (IWASAKI et al, 2009). Assim, a GSH é a forma encontrada em grande quantidade nas células sob condições normais e sua atividade antioxidante ocorre pela oxidação do grupo tiol em presença de H 2 O 2 gerando a glutationa oxidada (GSSG) pela ação da glutationa peroxidase (GIUSTARINI et al, 2009;GRIFFITH, 1999;GUTTERIDGE, 1995;MORAN;GUTTERIDGE;QUINLAN, 2001).…”
Section: Discussionunclassified